Integration of the XY-MD02 Module in an IoT-Based Humidity and Temperature Monitoring System with Graphic Display on Nextion LCD - Nor, Syafriyadi; Sarifudin, Sarifudin (Department of Electrical Engineering ITS and FORTEI, 2025)
Abstract—Temperature and humidity monitoring is crucial in various industrial sectors such as agriculture, manufacturing and health. Integrating the latest technology, such as IoT (Internet of Things), opens up new opportunities to increase the efficiency and accuracy of monitoring systems. This research focuses on integrating the XY-MD02 module into an IoT-based monitoring system to measure and monitor humidity and temperature levels accurately. The system uses the XY-MD02 module to collect data, which is transmitted wirelessly to the server using the MQTT protocol. The collected data is processed and displayed in real-time on the Nextion LCD, providing an intuitive graphical representation of environmental conditions. Integrating the XY-MD02 module and Nextion LCD in an IoT-based monitoring system demonstrates practical and reliable humidity and temperature measurements. The average value of the measured temperature is 31.58 with a standard deviation of 0.17, indicating high accuracy in temperature measurement with low variation. Meanwhile, for humidity, the average is 62.34, with a standard deviation of 1.01. The system's compatibility with the MQTT protocol ensures smooth communication and data exchange between devices. Integrating the XY-MD02 module in an IoT-based monitoring system has proven successful in providing accurate and real-time monitoring of humidity and temperature, offering an effective solution in environmental monitoring by keeping up with the latest technological developments.